Population Pharmacokinetic Quantification of CYP2D6 Activity in Codeine Metabolism in Ambulatory Surgical Patients for Model-Informed Precision Dosing - Ashraf, Muhammad Waqar; Poikola, Satu; Neuvonen, Mikko; Kiiski, Johanna I.; Kontinen, Vesa K.; Olkkola, Klaus T.; Backman, Janne T.; Niemi, Mikko; Saari, Teijo I. (Springer Science and Business Media LLC, 2025)
Background and Objective Codeine metabolism in humans is complex due to the involvement of multiple cytochrome P450 (CYP) enzymes, and has a strong genetic underpinning, which determines the levels of relevant CYP450 enzyme expression in vivo. Polymorphic CYP2D6 metabolises codeine to morphine via O-demethylation, while a strong correlation between CYP2D6 phenotype and opioidergic adverse efects of codeine is well documented. The aim of this study was to quantify the efect of CYP2D6 genotype on the biotransformation of codeine.
Methods We conducted a prospective clinical trial with 1000 patients, during which ambulatory patients were administered 60 mg of codeine preoperatively and the association between CYP2D6 activity and morphine exposure across various CYP2D6 genotypes was quantifed using a population pharmacokinetic model. Plasma concentration data for codeine and its primary metabolites were obtained from 997 patients and CYP2D6 genotype was screened for study subjects, and respective sums of activity scores assigned for each CYP2D6 allele were used as covariates in model development.
Results Our fnal model predicts the disposition of codeine and the formation of morphine, codeine-6-glucuronide and morphine-3-glucuronide adequately while accounting for variability in morphine exposure on the basis of CYP2D6 genotype. In agreement with previous results, patients with decreased function alleles (CYP2D6*10 and *41) showed varying levels of decrease in CYP2D6 activity that were inconsistent with increasing activity scores. Model simulations demonstrate that morphine concentrations in ultrarapid CYP2D6 metabolisers reach systemic concentrations that can potentially cause respiratory depression (over 9.1 ng/mL), and have 218% higher exposure (19 versus 8.7 µg · h/L, p < 0.001) to morphine than normal metabolisers. Similarly, poor and intermediate metabolisers had signifcantly reduced morphine exposure (1.0 and 3.7 versus 8.7 µg · h/L, p < 0.001) as compared with normal metabolisers.
Conclusions Our fnal model leads the way in implementing model-informed precision dosing in codeine therapy and identifes the use of genetic testing as an integral component in the efort to implement rational pharmacotherapy with codeine.